Torque ripple minimization in direct torque control at low-speed operation using alternate switching technique - Aihsan, Muhammad Zaid; Jidin, Auzani; Alias, Azrita; Ahmad Tarusan, Siti Azura; Md Tahir, Zuraidi; Sutikno, Tole (Institute of Advanced Engineering and Science, 2022)
Direct torque control (DTC) of induction motor is prominent to offer instant torque and flux control with a simple control structure. However, this scheme suffers from two major drawbacks namely high torque ripple and variable switching frequency of the inverter, especially during low-speed operation. During the low-speed condition, the positive torque slope is very steep and torque overshoot occurs frequently resulting in the torque ripple become of great significance. This paper proposes a new and effective technique to reduce the torque ripple by integrating the alternate switching technique to the inverter switching status to limit the torque slope surge. By varying the frequency and duty cycle of the alternate switching, the rate of surge can be controlled resulting in the chances of overshoots, and selection of reverse voltage vector can be avoided. The feasibility of the proposed technique has been validated using MATLAB/Simulink software and through experimental results. The results show the proposed alternate switching technique minimizes over 40% reduction in the torque ripple while maintaining the simple structure of DTC.